Ultra‐high‐field MRI using composite RF (STEP) pulses. (17th November 2020) - Ordidge, Roger; Cleary, Jon; Glarin, Rebecca; Blunck, Yasmin; Farquharson, Shawna; Moffat, Bradford
Abstract : Ultra‐high field MRI offers many opportunities to expand the applications of MRI. In order for this to be realized, the technical problems associated with MRI at field strengths of 7 T and greater need to be solved or mitigated. This paper explores the use of new variations of composite RF pulses, named serial transmit excitation pulses (STEP), in contrast to parallel pulse techniques, in order to remove and/or mitigate the effects of non‐uniform B 1 excitation fields associated with the subject (eg the human brain). Several techniques based on STEP sequences are introduced and their application to human brain imaging is presented and evaluated. Abstract : This paper explores new variations of composite RF pulses, named Serial Transmit Excitation Pulses (STEP) to remove and/or mitigate the effects of non‐uniform B1 excitation fields associated with the subject). The figure shows the improvement of signal strength (integrated across the imaging slice) for 90° and 180° sinc and STEP pulses versus B1 amplitude (sinc 90° normalized to 1.0). The application of STEP sequences to human brain imaging at 7 Tesla is presented and evaluated.